Foraging Behaviour of Stingless Bees (Tetragonula biroi) on Dombeya (Dombeya wallichii) (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This research investigates the growing interest in cultivating stingless bees (Tetragonula biroi), a species valued for producing honey, propolis, and pollen without the risk of stings. The study explores the interaction between these bees and Dombeya wallichii, a flowering plant that provides essential nectar and pollen resources. Conducted over a 12-day period in Pabuwaran Village, Banyumas, the research involved observing bee activity during three daily time intervals: morning, noon, and evening. The observations revealed that bee activity was most intense in the morning and evening, with the highest number of flower visits occurring in the morning. Interestingly, while the length of each visit tended to be longer during the daytime, statistical analysis using ANOVA showed no significant differences in the number of bees (p = 0.704) or visit durations (p = 0.426) across time periods. Despite the lack of statistically significant differences, there was an observable pattern suggesting that time of day could influence visitation behavior. Furthermore, regression analysis indicated that environmental variables—temperature, humidity, and light intensity—collectively had a statistically significant impact on bee activity (F = 3.896; p = 0.018). Among these factors, temperature emerged as the most influential, while humidity and light intensity did not show a significant individual effect. These findings contribute to a deeper understanding of the behavioral patterns of T. biroi and highlight the importance of specific environmental conditions in shaping their foraging behavior. The study’s insights are expected to support better management and optimization of stingless bee cultivation, offering practical value for sustainable apiculture and pollination strategies.